Protein and drug interactions in the minor groove of DNA - Morávek, Zdenek; Neidle, Stephen; Schneider, Bohdan (Nucleic acids research, 2002)
Interactions between proteins, drugs, water and B-DNA minor groove have been analyzed in crystal structures of 60 protein-DNA and 14 drug-DNA complexes. It was found that only purine N3, pyrimidine O2, guanine N2 and deoxyribose O4' are involved in the interactions, and that contacts to N3 and O2 are most frequent and more polar than contacts to O4'. Many protein contacts are mediated by water, possibly to increase the DNA effective surface. Fewer water-mediated contacts are observed in drug complexes. The distributions of ligands around N3 are significantly more compact than around O2, and distributions of water molecules are the most compact. Distributions around O4' are more diffuse than for the base atoms but most distributions still have just one binding site. Ligands bind to N3 and O2 atoms in analogous positions, and simultaneous binding to N3 and N2 in guanines is extremely rare. Contacts with two consecutive nucleotides are much more frequent than base-sugar contacts within one nucleotide. The probable reason for this is the large energy of deformation of hydrogen bonds for the one nucleotide motif. Contacts of Arg, the most frequent amino acid ligand, are stereochemically indistinguishable from the binding of the remaining amino acids except asparagine (Asn) and phenylalanine (Phe). Asn and Phe bind in distinct ways, mostly to a deformed DNA, as in the complexes of TATA-box binding proteins. DNA deformation concentrates on dinucleotide regions with a distinct deformation of the delta and epsilon backbone torsion angles for the Asn and delta, epsilon, zeta and chi for the Phe-contacted regions.
Keywords: vodíková vazba; Models, Chemical; Protein Binding; voda; Water; deoxyribonukleotidy; Nucleic Acid Conformation; chemické modely; konformace nukleové kyseliny; Amino Acids; dusík; kyslík; racionální návrh léčiv; Drug Design; Nitrogen; Binding Sites; Oxygen; aminokyseliny; Crystallography, X-Ray; Macromolecular Substances; DNA-Binding Proteins; makromolekulární látky; DNA; vazba proteinů; ligandy; Deoxyribonucleotides; vazebná místa; Hydrogen Bonding; DNA vazebné proteiny; Ligands; krystalografie rentgenová